New Technique for Tracking the Global Peaks of PV System under Partial Shaded Conditions - Ibrahim, A.E. (Institute of Electrical and Electronics Engineers Inc., 2021)
Partial Shaded Condition (PSC) is a process of non-optimal power capture in PV systems; this phenomenon occurs when one or more PV solar cells are shaded by external factors. It generates one global peak and many local peaks in the Power voltage curve. Thus, it makes a sudden change in cell irradiance and leads to non-optimal power capture in PV systems. In this work, a novel MPPT technique was proposed to solve the problem of tracking speed and accuracy in the shaded PV systems. FLC and GA-FLC with Power Scanning Technique (PST) algorithms were designed, developed and simulated using MATLAB/Simulink. The performance of FLC and GAFLC with PST was figured out under varied operating conditions. Proposed FLC tracked the PV power under PSC in 0. 4s with 92 accuracy, meanwhile, GA-FLC with PST achieved 0. 4s as tracking speed with 99 accuracy using Buck converter. Proposed GA-FLC with PST showed high capability in terms of tracking speed and accuracy compared to MPPT techniques. Finally, the dynamic performance of GA-FLC with the PST algorithm was compared to other techniques reported in the works of literature. Improved tracking speed and accuracy were obtained compared to other methods. For future work, experimental work in terms of tracking speed and accuracy should be carried out to validate the performance of the proposed algorithm. Â© 2021 IEEE.